Can Using Visual Images Enliven Teaching and Learning Within Closed Doors? (Bangladesh Journal of Educational Research, 2026)
Confinement to the home during the coronavirus pandemic changed teaching-learning dynamics for primary schoolers in Bangladesh and beyond. Early reports about homeschooling suggested that both parents and children experienced exhaustion and boredom. This qualitative study aimed to understand the workings of this newly evolved teaching-learning system and find whether visual images played any role. Semi-structured interviews were conducted with a convenience sample of three parents and three children. Twenty-nine significant statements were found, and six themes surfaced from them. Findings indicate that using visual images led to enjoyable learning amid lockdown. Parents also used them to engage their children with textual matter. Moreover, the study found that if parents had the time and could set aside their other responsibilities, they could break through the conventional teaching and learning spell that their children disliked. When that happened, the teaching-learning process shifted from its traditional, rigid form, where homework was the focus, to a playful, activity-based, and friendly form where visual images, games, and music prevailed.